Relação mãe ouvinte - filho surdo: o discurso das mães e a interação no brincar - Araújo, Camila Lamas Nunes de (2009)
Introduction: we know that deafness implications of deafness are a unique, because it difficult the basic mode of communication, which characterizes the humans from all other species, due to oral language. Play promotes greater approximation between parents and children in a nice and tranquil way, provides hearing parents a coexistence with their deaf child (Rossi, 2000). Play along strengthens the affective bonds causing the child feel your joke valued (Sheridan, 1990). Objective: the objective of this work is to describe the relationship child deaf mother listener, in a playful –therapy setting, analyzing mother’s speech and their interaction in a play situation. Method: this study is characterized as descriptive, qualitative and transversal and will be held with parents of deaf children's met in an institution of high complexity attendance, PUCSP/DERDIC/ECAC (Child Hearing Center). The sample was composed of 2 families of children with diagnosis of congenital hearing loss and 2 families of children with diagnosis of acquired hearing loss. The following procedures have been conducted with participants of this study: audio and video recording and transcription. The analysis of interviews was conducted from the speech of the subject collective (DSC) technique. Result: transcripts and analysed data have shown that mothers of children with congenital hearing loss have shown concern with development of children, expectations regarding the speech of children, both stimulate during the interaction and used as a means of communicative speech and gestures. Mothers of children with acquired hearing loss have demonstrated difficulty in communication and in interaction with their children, there has been no affectionate contact and little visual contact between mothers and children, mothers used signs and gestures as a means of communications. Both mothers demonstrated anguish and suffering. conclusion: regarding the situation of interaction in play, the relationship between mothers of children with congenital hearing loss was natural and spontaneous that seemed to occur in an enjoyable and affective way. Mothers realized in recreational and therapeutic recreational scenes large part of their speech. In this interaction there were more communicative intention than happened in scenes with the mothers of children with acquired hearing loss. Mothers of children with congenital hearing loss have explored more the gestures, the sights, the sounds, the speech, finally, these mothers have stimulated more frequently and accuracy than mothers of children with hearing loss